PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS DIGITAL BERBANTUAN BOOKCREATOR MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN IPAS KELAS V SEKOLAH DASAR - Falsy Rahalyu; Zuryanty Zuryanty; Aissy Putri Zulkarnaini; Hamimah Hamimah (Jurnal Manajemen Pendidikan, 2026)
This study aimed to develop digital learning media assisted by BookCreator and integrated with Problem Based Learning for fifth-grade IPAS learning, and to determine its validity and practicality. Methods: The study employed research and development using the ADDIE model, which included analysis, design, development, implementation, and evaluation. Needs analysis was conducted in four elementary schools, while product implementation involved three schools. The product was validated by material, media, and language experts. Practicality data were obtained from three fifth-grade teachers and 52 students using Likert-scale questionnaires and analyzed descriptively by percentage. Results: The developed product was a multimedia digital book on community economic activities that combined text, images, audio, video, guiding questions, problem scenarios, and quizzes in accordance with the Problem Based Learning syntax. Expert validation produced scores of 90% for material, 90% for media, and 84% for language, with an overall mean of 88%, categorized as highly valid. Teacher practicality scores were 96%, 96%, and 94%, while student practicality scores were 82%, 91%, and 90% across the three schools. All practicality results were classified as highly practical. Novelty: This study offers an integrated design that does not merely digitize content but organizes multimedia and learning activities around authentic economic problems, allowing BookCreator to function as a structured problem-solving environment for elementary IPAS learning. The media is therefore feasible as an alternative digital resource, although further testing of its effectiveness on learning outcomes and critical thinking is required.